1993
DOI: 10.1590/s0074-02761993000100016
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of American Cutaneous Leishmaniasis in a periurban area of the metropolitan region of Belo Horizonte, Minas Gerais, Brazil

Abstract: In order to characterize the epidemiology of American Cutaneous Leishmaniasis (ACL) in a periurban area of the municipality of Sabará in the metropolitan region of Belo Horizonte (MRBH), an area until then considered free of the disease, a cross sectional survey was undertaken in 1990. The survey of the population consisted of 1119 interviews and 881 clinical examinations using Montenegro's skin test (MST). A low prevalence (3.7%) of positive MST was encountered. The disease had been occurring in the area for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
16

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 0 publications
3
31
0
16
Order By: Relevance
“…Passos et al (1998) performed an entomological survey in the Boa Vista quarter, a suburban area of BH, and in the district of Venda Nova, where the presence of Lutzomyia whitmani and L. longipalpis, the insect vectors of ACL and visceral leishmaniasis (VL), respectively, had been reported. Such studies associated with recent publications have confirmed VL (Silva et al 2001) and ACL (Passos et al 1993(Passos et al , 2001) urbanization in BH.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Passos et al (1998) performed an entomological survey in the Boa Vista quarter, a suburban area of BH, and in the district of Venda Nova, where the presence of Lutzomyia whitmani and L. longipalpis, the insect vectors of ACL and visceral leishmaniasis (VL), respectively, had been reported. Such studies associated with recent publications have confirmed VL (Silva et al 2001) and ACL (Passos et al 1993(Passos et al , 2001) urbanization in BH.…”
supporting
confidence: 72%
“…Previous investigations have proven that the single use of CDC traps does not allow the identification of phlebotomine fauna concerning its quantitative and qualitative features (Azevedo et al 2002, Oliveira et al 2003. Based on the results of the current work, the use of Shannon traps allowed us to evaluate the presence of some species that were not collected (Passos et al 1993) and it has been shown to be highly sensitive in detecting protozoa parasites into phlebotomine sand flies (Rodriguez et al 1999, Miranda et al 2002, Michalsky et al 2002. Nevertheless, previous reports have shown that phlebotomine infectivity rates in nature are low, 0.2 to 2%, making the parasite finding difficult (Rodriguez et al 1999, Miranda et al 2002.…”
Section: Discussionmentioning
confidence: 80%
“…A fauna de flebotomíneos do município de Montes Claros, foi constituída de 16 espécies, sendo elas: urbanização, áreas sem condição de moradia adequada, e consequentemente a presença de cães infectados, propiciando a adaptação da Leishmania ao novo nicho ecológico 21 . As epidemias registradas em importantes centros urbanos do país evidenciam como o processo migratório do campo para as grandes cidades influenciou na mudança do perfil epidemiológico da LV 27 .…”
Section: Resultsunclassified
“…Nas Américas, a LV ocorre desde o México até a Argentina, sendo que cerca de 90% dos casos humanos descritos são procedentes do Brasil 16 . A LV apresenta amplo espectro epidemiológico no mundo, ocorrendo em vastas áreas tropicais e subtropicais do globo, podendo apresentar-se como zoonose, antroponose ou antropozoonose, estas duas últimas, quando o homem atua como reservatório no ciclo de transmissão do parasito 21 .…”
unclassified
“…The value of rp calculated from previous cross-sectional studies varies considerably, for example: 0-02 [16], 0 03 [17], 0 07 [11], 0-11 [18], 0-22 [19], 0-25 [12], 0-67 [20], and 1-0 [21].…”
Section: Introductionmentioning
confidence: 99%